Adv Crop Sci Tech 2016
DOI: 10.4172/2329-8863.1000215
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vitro Rooting of Sugarcane (Saccharum officinarum L.) Plantlets Derived from Tissue Culture

Abstract: A study was conducted at Holetta National Agricultural Biotechnology Laboratory with the objective to determine the effect of different concentrations of NAA on ex vitro root development of sugarcane microshoots. Five levels of NAA (0, 10, 20, 30 and 40 mg/l) and two levels of genotypes were combined in factorial arrangement. The basal end of the shoots was dipped in NAA solution overnight before the shoots were transferred into a plastic tray containing a mixed growing medium in green house. The results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…However, the use of indole-butyric acid applied in the form of talc for the rooting of sugarcane mini-cuttings has not yet been reported in the literature. Tesfa et al (2016), when studying ex vitro rooting of sugarcane plants derived from micropropagation, observed that the treatment of shoots with solution containing 20 mg L -1 of naphthalene-acetic acid for 24 hours increased rooting by 40% when compared to the control without regulator.…”
Section: Resultsmentioning
confidence: 99%
“…However, the use of indole-butyric acid applied in the form of talc for the rooting of sugarcane mini-cuttings has not yet been reported in the literature. Tesfa et al (2016), when studying ex vitro rooting of sugarcane plants derived from micropropagation, observed that the treatment of shoots with solution containing 20 mg L -1 of naphthalene-acetic acid for 24 hours increased rooting by 40% when compared to the control without regulator.…”
Section: Resultsmentioning
confidence: 99%